2021
DOI: 10.1038/s41419-021-04050-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional CDK inhibitors, CYC065 and THZ1 promote Bim-dependent apoptosis in primary and recurrent GBM through cell cycle arrest and Mcl-1 downregulation

Abstract: Activation of cyclin-dependent kinases (CDKs) contributes to the uncontrolled proliferation of tumour cells. Genomic alterations that lead to the constitutive activation or overexpression of CDKs can support tumourigenesis including glioblastoma (GBM), the most common and aggressive primary brain tumour in adults. The incurability of GBM highlights the need to discover novel and more effective treatment options. Since CDKs 2, 7 and 9 were found to be overexpressed in GBM, we tested the therapeutic efficacy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Furthermore, paediatric tissues are more primed to apoptosis-inducing stimuli than corresponding adults [ 71 ] and more susceptible to damage. A potential solution is to indirectly target BCL-2 family proteins, for example with the CDK inhibitors Seliciclib [ 77 ], Dinaciclib [ 78 ], or THZ1 [ 67 ], which suppress MCL-1 levels. Secondly, ongoing development of more targeted inhibitors is addressing the lack of cancer-cell specificity of current BH3 mimetics.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, paediatric tissues are more primed to apoptosis-inducing stimuli than corresponding adults [ 71 ] and more susceptible to damage. A potential solution is to indirectly target BCL-2 family proteins, for example with the CDK inhibitors Seliciclib [ 77 ], Dinaciclib [ 78 ], or THZ1 [ 67 ], which suppress MCL-1 levels. Secondly, ongoing development of more targeted inhibitors is addressing the lack of cancer-cell specificity of current BH3 mimetics.…”
Section: Discussionmentioning
confidence: 99%
“…CDKs play a critical role in regulating the cell cycle along with corresponding regulatory cyclins by controlling the progression of cells through the different stages of the cell cycle [ 29 , 30 ]. In particular, cyclin D1 is involved in the G 0 /G 1 cell cycle arrest, while cyclin E1 and CDK2 control the progression from the G 1 to the S phase.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of the difference in sensitivity of MFB between tumor cells and non-tumor Hacat keratinocytes remains to be investigated. It has been described that cell doubling time may affect sensitivity to chemotherapeutic agents ( 55 ). In addition, several studies have suggested that VEGFRs may be expressed by tumor cells, although VEGFRs are regarded as endothelial receptors.…”
Section: Discussionmentioning
confidence: 99%